STUDENTS’ WRITING SKILL IN USING COHESION AND COHERENCE ON DESCRIPTIVE ESSAY - Niati, Batdal; Jannah, Wirda Jannatul; Anggini, Dita (JEE (Journal of English Education), 2023)
This research aimed to know how students’ skill in writing descriptive essay and what types of cohesion and the ways to achieve coherence used on descriptive essay. It was quantitative research. Total sample was 36 students. In collecting the data, the researcher used a writing test. Writing components were used to analyze data; Content, Organization, Vocabulary, Language Use, Mechanic and then analyze the result of the types cohesion. The findings showed that the students' skill in writing descriptive essays was in the fair level with the score 69,31 with content 21.01 score had the fair to poor level, organization with 14.52 score had the good to average level, vocabulary with 14 score had good to average level, language use with 16.74 score had fair to poor level and in mechanics with 3.34 score had fair to poor level and the types of cohesion used were 60,50% used reference on their descriptive essay and followed by 31,55 % conjunction, 5,51 % substitution, 1,35 % reiteration, 0,96 % collocation, and 0.09 % ellipsis. Then, in the ways to achieve coherence also used 61,42 % repeating key nouns, 31,69% used consistent pronoun, 4,42% used transition signals to link ideas and 2,45% in arranging ideas in logical order. It meant that students were quite capable of writing descriptive essay and they had used all of the types of cohesion and the ways to achieve coherence but they still need to be improved.